What should I eat? Experimental evidence for prey selection in grey seals. (January 2017) - Gallon, Susan L.; Thompson, Dave; Middlemas, Stuart J.
Abstract : Understanding the responses of predators, such as seals, to variations in prey availability is key to understanding their role in marine ecosystems. Individual variation in prey preference is likely to be important but we have little information on this aspect of predator behaviour. Operant conditioning techniques and an underwater feeding apparatus were used to test the prey species and size preferences of five captive grey seals, Halichoerus grypus, in a series of paired choice trials. The experimental procedure was designed to present simple foraging choices to remove as many potentially confounding variables as possible. Results suggest that individual grey seals exhibit prey preferences. When presented with different numbers of items of the same species, seals generally selected the larger number of prey items. When presented with choices between two species, seals apparently showed consistent preferences for particular species. However, the apparent species preferences may be simply explained in terms of size selection. Highlights: Paired choice experiments were used to examine prey preferences in grey seals. For choices between the same prey, seals tended to maximize the numbers chosen. For choices between prey species, individuals showed preferences for particular prey. Preference of prey species may be the result of size selection linked to handling time.